Novel Synthesis of Gold Doped Silver Phosphate Nanoparticles by Hydrothermal Method for The Enhancement of Visible Light-Responsive Photocatalytic Degradation of Fast Green FCF Dye - Qasim, Amin Kalo (Science Journal of University of Zakho, 2022)
In this study, the gold (Au) noble metal doped Ag3PO4 nanoparticles (NPs) were synthesized by hydrothermal method. The obtained photocatalysts NPs were characterized via FE-SEM, EDX, XRD and UV-Vis spectrophotometer. The crystal structure and phase were identified by XRD characterization. From the XRD the structure of Ag3PO4 NPs was not altered after doping with Au as a noble metal; in addition the sharp and narrow peaks indicate that Ag3PO4 NPs are high purity and have a crystalline structure. And the XRD pattern of samples after doping indicates that Au distributed homogenously in Ag3PO4. The morphology of bare Ag3PO4 and Au doped Ag3PO4 were studied by FE-SEM. The average sizes of the synthesized Ag3PO4 and Au doped Ag3PO4 NPs were 747.81 nm and 96.77nm respectively. EDX is utilized for the elemental composition analysis of the synthesized NPs and the pattern consists of corresponding peaks for P, Ag, O, and Au ions and it confirms the doped of Au noble metal ion in the prepared samples . The optical properties and the band gap were estimated by UV-Vis spectrophotometer. The band gap was found for undoped and doped Ag3PO4 NPs were 2.39 eV and 2.34 eV respectively. Furthermore, the photocatalytic performances for bare Ag3PO4 NPs and Au doped Ag3PO4 were studied with fast green FCF dye. As a result the Au@ Ag3PO4 could be considered the optimum photocatalyst because the target dye molecule is degraded in 15 min, in contrast the bare Ag3PO4 NPs needed 55min. The photo degradation rate of the Au@ Ag3PO4 NPs is ∼3 times higher than the rate of Ag3PO4 NPs. Finally, Au@ Ag3PO4 NPs confirmed the highest photodegradation catalyst compared with other bare Ag3PO4 NPs.